Use of day services improved cognitive function in patients with Alzheimer's disease. Issue 5 (5th May 2020) - Honjo, Yasuyuki; Ide, Kazuki; Takechi, Hajime
Abstract : Aim: Day services (DS) are part of the public nursing care system in Japan. The purpose of DS is to help elderly individuals maintain mental and physical functions, eliminate feelings of isolation among homebound users, and reduce the burden of care on family members. However, the relationship between DS and the progression of Alzheimer's disease (AD) remains unclear. Methods: We retrospectively analyzed 161 AD patients based on available Mini‐Mental State Examination (MMSE) scores. The patients were divided into two groups: those who started to use DS ( n = 106) and those who did not use DS ( n = 55). We then compared the groups' MMSE scores between the first memory clinic visit and the 6‐month point. Results: There were no significant differences between the two groups with regard to sex and the number of family members, but the non‐DS group was younger, had more education, and had better MMSE scores at the first visit. At 6 months, we found a significant improvement in the MMSE scores of DS users, reflecting improved cognitive function. In addition, lower MMSE score at the first visit was associated with greater improvement in MMSE score at 6 months. Interestingly, the frequency of DS use had no significant effect on MMSE score. However, after approximately 6 months, DS use significantly improved the cognitive function of AD patients. Conclusions: DS use significantly improved the cognitive function of AD patients. However, most DS users in Japan are older and have severe dementia. Patients who are younger, have more education, or have mild dementia dislike using DS. As a significant difference was found in the MMSE scores between the two groups after 6 months, DS use appears to be a useful non‐drug therapy.